Study protocol for a multicentre, controlled non-randomised trial: benefits of exercise physiology services for type 2 diabetes (BEST). Issue 8 (21st August 2019) - Kitic, Cecilia M; Selig, Steve; Davison, Kade; Best, Tania L B; Parmenter, Belinda; Pumpa, Kate; Furzer, Bonnie; Rice, Vanessa; Hardcastle, Sibella; Cheney, Michael; Palmer, Andrew J; Fraser, Steve; et al.
Abstract : Introduction: Controlled trials support the efficacy of exercise as a treatment modality for chronic conditions, yet effectiveness of real-world Exercise Physiology services is yet to be determined. This study will investigate the efficacy and cost-effectiveness of services provided by Accredited Exercise Physiologists (AEPs) for clients with type 2 diabetes (T2D) in clinical practice. Methods and analysis: A non-randomised, opportunistic control, longitudinal design trial will be conducted at ten Exercise Physiology Clinics. Participants will be individuals with T2D attending one of the Exercise Physiology Clinics for routine AEP services (exercise prescription and counselling) (intervention) or individuals with T2D not receiving AEP services (usual care) (control). The experimental period will be 6 months with measurements performed at baseline and at 6 months. Primary outcome measures will be glycosylated haemoglobin (HbA1c), resting brachial blood pressure (BP), body mass index, waist circumference, 6 min walk test, grip strength, 30 s sit to stand, Medical Outcomes Short-Form 36-Item Health Survey and Active Australia Questionnaire. Secondary outcomes will be medication usage, out-of-pocket expenses, incidental, billable and non-billable health professional encounters and work missed through ill health. Healthcare utilisation will be measured for 12 months prior to, during and 12 months after trial participation using linked data from Medicare Benefits Schedule and Pharmaceutical Benefits Scheme data. Ethics and dissemination: The study is a multicentre trial comprising: University of Tasmania, University of New South Wales Lifestyle Clinic, University of Canberra, Baker Heart and Diabetes Institute (covered under the ethics approval of University of Tasmania Health and Medical Ethics Committee H0015266), Deakin University (Approval number: 2016–187), Australian Catholic University (2016–304R), Queensland University of Technology (1600000049), University of South Australia (0000035306), University of Western Australia (RA/4/1/8282) and Canberra Hospital (ETH.8.17.170). The findings of this clinical trial will be communicated via peer-reviewed journal articles, conference presentations, social media and broadcast media. Trial registration number: ACTRN12616000264482.